Jenis-Jenis Gastropoda di Kawasan Hutan Mangrove Muara Sungai Kuala Baru Kecamatan Jawai Kabupaten Sambas - Ari Hepi Yanti, Darmi, Tri Rima Setyawati (Jurnal Protobiont, 2017)
The Gastropodsis the most members of the phylum Mollusca and is most prevalent of aquatic and terrestrial habitats. This research aims to identify the Gastropods found in the mangrove forest area of Kuala Baru River Estuary. The research was carried out from January to March 2016. The Gastropods collected included treefauna, epifauna and infauna. The Gastropods of treefauna and epifauna were collected using the square transect method and the Gastropodsof infauna using hand sorting method. There were 12 genera of Gastropods found belonging to 9 families i.e. Ellobiidae, Potamididae, Neritidae, Ampullariidae, Pomatiopsidae, Littorinidae, Strombidae, Nassariidae and Olividae. The Ellobiidae are the mostmembers that often found in the mangrove forest area of Kuala Baru River Estuary. There were only four genera of Gastropods which were found in more than one station i.e.the Cassidula as many as 167 individuals, Pythia 21 individuals, Cerithidea 19 individuals and Terebralia 209 individuals. The Gastropods most commonly found each station is epifauna.